(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article discusses the influence of public consciousness on the spiritual revival and development of the country, in addition, as stated in it, it is necessary to dialectically consider the revival of traditional society as a process accompanied by a change in the value components of public consciousness and the adoption of innovations. In this process, the transfer of traditional value orientations is considered as a mechanism of social development that combines the main characteristics of continuity and variability at the same time. For example, the discourse of a traditional society focuses primarily on the path to the goal. For a person of a traditional society, methods, means, resources or forms of activity that are sacred in nature are important